Bonding strategies for MIH-affected enamel and dentin. Issue 2 (February 2018) - Krämer, Norbert; Bui Khac, Ngoc-Han Nana; Lücker, Susanne; Stachniss, Vitus; Frankenberger, Roland
Abstract: Objectives: Aim of the present study was to evaluate resin composite adhesion to dental hard tissues affected by molar incisor hypomineralisation (MIH). Methods: 94 freshly extracted human molars and incisors (53 suffering MIH) were used. 68 teeth (35 with MIH) were used for μ-TBS tests in enamel and dentin, 26 (18 with MIH) for qualitative evaluation. Specimens were bonded with Clearfil SE Bond, Scotchbond Universal, and OptiBond FL. For MIH affected enamel, additional OptiBond FL groups with NaOCl and NaOCl + Icon were investigated. Beside fractographic analysis, also qualitative evaluations were performed using SEM at different magnifications as well as histological sectioning. Results: Highest μ-TBS values were recorded with dentin specimens (ANOVA, mod. LSD, p < 0.05). Results were independent of adhesive and dentin substrate (p > 0.05). Pre-test failures did not occur in dentin specimens. Sound enamel specimens exhibited significantly higher μ-TBS values than MIH enamel (p < 0.05). The two-step self-etch adhesive (Clearfil SE Bond) and the two-step etch-and-rinse adhesive (Scotchbond Universal) showed the lowest values in affected enamel specimens (p < 0.05) with most pre-test failures (p < 0.05). OptiBond FL on affected enamel showed better results than Clearfil SE Bond (p < 0.05). An additional pre-treatment of affected enamel with NaOCl or NaOCl and Icon did not enhance enamel bonding (p > 0.05), however, it caused less pre-test failures (p < 0.05). Micromorphological analyses revealed that conventional phosphoric acid etching produces a much less pronounced etching pattern in affected enamel and a porous structure as weak link for the resin-enamel bond was identified. Significance: Bonding to porous hypomineralized MIH enamel is the limiting factor in adhesion to MIH teeth. MIH-affected dentin may be bonded conventionally.